Debating Levinas' legacy - Breitling, Andris.; Bremmers, Chris.; Cools, Arthur, 1967- (Studies in Contemporary Phenomenology, 2015)
The contributions of this volume discuss the legacy of Emmanuel Levinas' philosophy. Examining critically the limits of his thinking, they also bear witness to its influence on contemporary philosophy, thus demonstrating the significance of his groundbreaking project of establishing ethics as first philosophy. In four parts, "First Philosophy, Phenomenology, and Ethics," "Phenomenology and its Theological Turn?," "Ethics and Aesthetics," "Phenomenology, Hermeneutics, Deconstruction," the major themes in Levinas' oeuvre are addressed, such as alterity, human dignity, religion, and communication. Contributors: Thomas Baumeister, Andris Breitling, Roger Burggraeve, Arthur Cools, Sylvie Courtine-Denamy, Eddo Evink, Matthias Flatscher, Gert-Jan van der Heiden, Alwin Letzkus, Burkhard Liebsch, Michel Lisse, Stefano Micali, Marcel Poorthuis, Renée van Riessen, Johan Taels, László Tengelyi, Rudi Visker, Jacques de Visscher, Elisabeth Weber.